(untitled) (Efficient: Indonesian Journal of Development Economics, 2026)
This study aims to analyze the application of the circular economy in micro, small, and medium enterprises (MSMEs) in the food and beverage sector in Central Java Province and formulate an efficient and sustainable ecosystem development model. The research employed an exploratory descriptive method with a case study approach, examining 60 business units across four districts/cities: Semarang, Semarang Regency, Kendal, and Kudus. The analysis was conducted using a circular economy calculator to measure four key indicators: circularity, value capture, recycled content, and reuse index. The results showed that the circularity level in food MSMEs was still low, with 75.5% of respondents falling within the range of 1-5%. Most of the value capture, recycling content, and reuse index scores were also below 1%. This condition reflects the limitations of knowledge, access to technology, and the availability of adequate waste management infrastructure.